Dual-energy CT-cholangiography in potential donors for living-related liver transplantation: improved biliary visualization by intravenous morphine co-medication - Sommer, Christof-Matthias; Schwarzwälder, Christoph Bernhard; Stiller, Wolfram; Heye, Tobias; Stampfl, Ulrike; Bellemann, Nadine; Holzschuh, Maria; Schmidt, Jan; Weitz, Jürgen; Grenacher, Lars; Kauczor, Hans-Ulrich; Radeleff, Boris (European journal of radiology, 2012)
Purpose: To prospectively evaluate whether intravenous morphine co-medication improves bile duct visualization of dual-energy CT-cholangiography. Materials and methods: Forty potential donors for living-related liver transplantation underwent CT-cholangiography with infusion of a hepatobiliary contrast agent over 40min. Twenty minutes after the beginning of the contrast agent infusion, either normal saline (n=20 patients; control group [CG]) or morphine sulfate (n=20 patients; morphine group [MG]) was injected. Forty-five minutes after initiation of the contrast agent, a dual-energy CT acquisition of the liver was performed. Applying dual-energy post-processing, pure iodine images were generated. Primary study goals were determination of bile duct diameters and visualization scores (on a scale of 0 to 3: 0—not visualized; 3—excellent visualization). Results: Bile duct visualization scores for second-order and third-order branch ducts were significantly higher in the MG compared to the CG (2.9±0.1 versus 2.6±0.2 [P<0.001] and 2.7±0.3 versus 2.1±0.6 [P<0.01], respectively). Bile duct diameters for the common duct and main ducts were significantly higher in the MG compared to the CG (5.9±1.3mm versus 4.9±1.3mm [P<0.05] and 3.7±1.3mm versus 2.6±0.5mm [P<0.01], respectively). Conclusion: Intravenous morphine co-medication significantly improved biliary visualization on dual-energy CT-cholangiography in potential donors for living-related liver transplantation.
Available online 21 June 2011
Gesehen am 25.07.2018